Effects of Bt (Bacillus thuringiensis) Corn on Reproductive Performance in Adult Laying Hens - Rasmussen, Mark A.; Cutler, Sara A.; Wilhelms, Kelly; Scanes, Colin G. (International Journal of Poultry Science, 2007)
Genetically Modified (GM) crops are widely used. Research has focused on examining differences between GM and conventional corn feeding on broiler performance and carcass composition. However, relatively little attention has been focused on reproductive effects on the recipient animals. To address this, the present study employed laying hens as a model due to their rapid reproductive development and rate of egg production. This study investigated the putative effects of a diet consisting of Starlink corn (expressing the Bacillus thuringiensis gene Cry9C) on the fecundity of the laying hen. Twenty-week-old point of lay pullets were fed a diet containing corn positive for the Cry9C (Starlink) gene (not a current variety) for 3 weeks, paired with a corn-based diet known not to contain the gene. During the study, the number of eggs collected, egg shell thickness, number of yolks and egg weight and, upon necropsy, body, ovary and ovary weight, together with the number of yolky (yellow) follicles were recorded. There were no negative effects observed on any parameter measured. The present data do not suggest that Bt corn is a cause of concern to the poultry or livestock industry.